TiO2-co-tio3 hollow nanoreactor and preparation method and application thereof
Patent Information
- Application Number
- CN202410299948.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-15
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-03-15
AI Technical Summary
Existing cobalt-based catalysts are prone to agglomeration and cobalt ion shedding during persulfate activation, resulting in reduced catalytic activity and secondary pollution problems. Traditional cobalt titanate materials are large in size, have few exposed active sites, and have insignificant catalytic activity.
Using RF microspheres as templates, cobalt ions are applied to the surface of amorphous TiO2 via ion exchange to form a TiO2-CoTiO3 hollow nanoreactor. CoTiO3 nanoparticles with a size of 11-13 nm are uniformly distributed on the hollow structure of TiO2. CoTiO3 particles are formed in situ by ion exchange and high-temperature treatment.
Uniform loading of CoTiO3 nanoparticles was achieved, exposing a large number of active sites and improving the activation efficiency of persulfate. The hollow structure increased the reactant concentration, promoted the catalytic reaction, and significantly degraded tetracycline hydrochloride. The catalyst also exhibited good cycle stability.
Smart Images

Figure CN118287058B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalytic materials technology. This invention relates to a TiO2-CoTiO3 hollow nanoreactor, its preparation method and application. Background Technology
[0002] Advanced oxidation technologies based on persulfate activation have significant application prospects in wastewater treatment due to their strong oxidation capacity and wide pH operating range. Cobalt-based catalysts have been proven to be highly efficient for persulfate activation; however, single catalyst materials are prone to aggregation and cobalt ion loss during the reaction, resulting in reduced catalytic activity and secondary pollution problems.
[0003] In recent years, perovskite materials have attracted widespread attention due to their structural stability. Among them, cobalt-containing perovskite materials (such as cobalt titanate) can be used for the activation of persulfate. Cobalt titanate materials synthesized by traditional methods are generally large in size, typically in the submicron range, resulting in limited exposure of active sites and insignificant catalytic activity. Therefore, synthesizing small-sized cobalt titanate nanoparticles and loading them onto suitable supports is of significant practical importance for their efficient activation of persulfate for the degradation of organic pollutants. Summary of the Invention
[0004] The purpose of this invention is to provide a TiO2-CoTiO3 hollow nanoreactor. Using RF microspheres as a template, cobalt ions are introduced onto the surface of amorphous TiO2 via ion exchange, creating a strong interaction between the two. Following in-situ reaction under high-temperature air treatment, the TiO2-CoTiO3 hollow nanoreactor is obtained. TiO2 serves both as a carrier for dispersing CoTiO3 and as a reactant required for CoTiO3 formation. The RF microsphere template is converted into a gas and released during high-temperature air treatment, eliminating the need for additional template removal. The CoTiO3 nanoparticles, with a size of 11–13 nm, are uniformly distributed on the hollow TiO2 structure, which facilitates the exposure of active sites and efficient activation of persulfate.
[0005] Another objective of this invention is to provide a method for preparing a TiO2-CoTiO3 hollow nanoreactor.
[0006] Another object of the present invention is to provide an application of a TiO2-CoTiO3 hollow nanoreactor in the activation of persulfate to degrade tetracycline hydrochloride.
[0007] The technical solution to achieve the objective (1) of this invention is: a TiO2-CoTiO3 hollow nanoreactor, wherein the material is a hollow structure, the CoTiO3 nanoparticles are 11-13 nm in size, and are uniformly loaded on the surface of the TiO2 hollow structure.
[0008] The technical solution to achieve the objective (2) of this invention is: a method for preparing a TiO2-CoTiO3 hollow nanoreactor, the method comprising the following specific steps:
[0009] Step 1: Mix anhydrous ethanol, deionized water, concentrated ammonia, resorcinol, and formaldehyde solution, stir, centrifuge, and wash to obtain RF template microspheres;
[0010] Step 2: Disperse RF template microspheres in anhydrous ethanol, add acetonitrile, hydroxypropyl cellulose and concentrated ammonia, then add a mixed solution of tetrabutyl titanate-ethanol-acetonitrile, stir for a period of time, centrifuge and wash to obtain RF@TiO2 core-shell structure material;
[0011] Step 3: Disperse the RF@TiO2 core-shell structured material in NaOH solution, stir for a certain time, centrifuge, and disperse the resulting product in deionized water;
[0012] Step 4: Add cobalt chloride solution to the suspension obtained in step 3, stir for a period of time, centrifuge and wash, and then dry.
[0013] Step 5: Treat the product obtained in step 4 at high temperature in air for a period of time, disperse the high-temperature treated sample in hydrochloric acid solution, stir for a period of time, centrifuge, wash and dry to obtain TiO2-CoTiO3 hollow nanoreactor.
[0014] Preferably, in step 1, the ratio of anhydrous ethanol to resorcinol is 0.1 mL:1 mg to 0.4 mL:1 mg; the ratio of deionized water to resorcinol is 0.2 mL:1 mg to 0.8 mL:1 mg; the ratio of concentrated ammonia to resorcinol is 2 μL:1 mg to 4 μL:1 mg; the mass concentration of formaldehyde solution is 37%, and the ratio of formaldehyde solution to resorcinol is 1 μL:1 mg to 2 μL:1 mg; the stirring time is 6-12 hours.
[0015] Preferably, in step 2, the ratio of anhydrous ethanol to resorcinol in step 1 is 0.2 mL:1 mg to 0.3 mL:1 mg, and the ratio of acetonitrile to resorcinol in step 1 is 0.07 mL:1 mg to 0.09 mL:1 mg; the mass ratio of hydroxypropyl cellulose to resorcinol in step 1 is 0.5:1 to 0.6:1, and the ratio of concentrated ammonia to resorcinol in step 1 is 2 μL:1 mg to 4 μL:1 mg; in the mixed solution of tetrabutyl titanate-ethanol-acetonitrile, the volume ratio of tetrabutyl titanate, ethanol, and acetonitrile is 1:3:1, and the ratio of tetrabutyl titanate to resorcinol in step 1 is 10 μL:1 mg to 15 μL:1 mg; the stirring time is 2 hours.
[0016] Preferably, in steps 1 and 2, the mass concentration of concentrated ammonia is 26% to 28%.
[0017] Preferably, in step 3, the concentration of the NaOH solution is 0.1-0.3 mol / L, the ratio of NaOH solution to resorcinol mentioned in step 1 is 0.1 mL: 1 mg to 0.2 mL: 1 mg, the stirring time is 0.5-1.0 hours, and the ratio of deionized water used for dispersion to resorcinol mentioned in step 1 is 0.1 mL: 1 mg to 0.2 mL: 1 mg.
[0018] Preferably, in step 4, the concentration of the cobalt chloride solution is 0.5-1.0 mol / L, and the ratio of the cobalt chloride solution to the resorcinol mentioned in step 1 is 10 μL: 1 mg to 20 μL: 1 mg; the stirring time is 12-24 hours.
[0019] Preferably, in step 5, the mixture is treated at a high temperature of 600-800℃ in air for 4 hours; the concentration of the hydrochloric acid solution is 0.01-0.1mol / L, and the ratio of the hydrochloric acid solution to the resorcinol mentioned in step 1 is 0.1mL:1mg to 0.2mL:1mg; the stirring time is 8-16 hours.
[0020] The technical solution to achieve the objective (3) of this invention is: the application of the TiO2-CoTiO3 hollow nanoreactor in the degradation of tetracycline hydrochloride by activated persulfate, with reaction conditions of catalyst concentration of 0.2-1.0 g / L, persulfate concentration of 0.2-1.0 g / L, and tetracycline hydrochloride concentration of 5-50 mg / L.
[0021] Compared with the prior art, the present invention has the following significant advantages: (1) It provides a simple ion exchange method and high temperature treatment process for synthesizing TiO2-CoTiO3 hollow nanoreactors. The microsphere template can be removed during high temperature treatment without additional template removal operation. TiO2 serves as both a carrier for dispersing CoTiO3 and a reactant required for the formation of CoTiO3. (2) The particle size of CoTiO3 is 11-13 nm, which is significantly lower than the submicron size reported in the literature. The small-sized perovskite CoTiO3 is conducive to the large-scale exposure of active sites and the activation of persulfate. (3) The hollow nanoreactor has a certain confined space. The adsorption of reactants by the hollow structure can form a high concentration of reactant molecules in the confined space, which is conducive to promoting the catalytic reaction. (4) TiO2 and CoTiO3 have a relatively good lattice match. Ion exchange and high temperature treatment can make the two have a strong interaction, which is helpful for its stability and electron transfer with persulfate. Attached Figure Description
[0022] Figure 1 This is a transmission electron microscope image of the TiO2-CoTiO3 hollow nanoreactor synthesized in Example 1.
[0023] Figure 2 The images show the morphology and elemental distribution of the TiO2-CoTiO3 hollow nanoreactor synthesized in Example 1: (a) HAADF-STEM image; (b) Ti elemental distribution map; (c) O elemental distribution map; (d) Co elemental distribution map.
[0024] Figure 3 The image shows the X-ray diffraction pattern of the TiO2-CoTiO3 hollow nanoreactor synthesized in Example 1.
[0025] Figure 4 The images show the effect of activated persulfate on the degradation of tetracycline hydrochloride in the samples synthesized in Example 1, Comparative Example 1, and Comparative Example 2.
[0026] Figure 5 The image shows the cycling effect of activated persulfate on tetracycline hydrochloride in the sample synthesized in Example 1.
[0027] Figure 6 The images show the effect of activating persulfate to degrade tetracycline hydrochloride using the TiO2-CoTiO3 hollow nanoreactor synthesized in Examples 2-6.
[0028] Figure 7 This is a schematic diagram illustrating the preparation principle of the TiO2-CoTiO3 hollow nanoreactor of the present invention. Detailed Implementation
[0029] The technical solution of the present invention will be described in detail below with reference to the embodiments and accompanying drawings.
[0030] This invention utilizes hollow TiO2 as a carrier, embedding CoTiO3 nanoparticles into the hollow structure through in-situ reactions involving ion exchange and high-temperature treatment. The resulting CoTiO3 particles have a size of 11-13 nm, significantly smaller than the submicron size reported in current literature. The synthesis of small-sized CoTiO3 particles facilitates the exposure of active sites, playing a crucial role in fully utilizing the cobalt atoms on their surface to activate persulfate. Furthermore, the hollow structure possesses a high specific surface area, which can increase the reactant concentration around the nanoreactor by adsorbing reactant molecules, thereby promoting the catalytic reaction.
[0031] The principle of this invention is as follows: After amorphous titanium dioxide is treated with sodium hydroxide, the sodium ions on its surface can exchange with other ions. This exchange with cobalt ions allows the cobalt ions to act on the TiO2 surface. Then, high-temperature treatment in an air atmosphere causes the cobalt ions to react with TiO2 to form CoTiO3 particles, which are then in situ loaded onto the TiO2 shell. Finally, treatment with hydrochloric acid yields the final TiO2-CoTiO3 hollow nanoreactor. A schematic diagram of its preparation is shown below. Figure 7As shown, the role of sodium hydroxide in the preparation of TiO2-CoTiO3 hollow nanoreactors is to treat the TiO2 surface with sodium hydroxide to form Ti-O-Na. + During subsequent ion exchange, cobalt ions can firmly adhere to the TiO2 surface. Therefore, without sodium hydroxide treatment, cobalt ions cannot effectively adhere to the TiO2 surface, meaning that CoTiO3 nanoparticles cannot be formed in situ through subsequent reactions. Furthermore, TiO2 serves both as a carrier for dispersing CoTiO3 and as a reactant required for CoTiO3 formation. The RF microsphere template becomes a gas and escapes during high-temperature treatment in air, eliminating the need for additional template removal. In particular, treating the sample with hydrochloric acid can remove unstable cobalt species from the surface of the TiO2-CoTiO3 hollow nanoreactor, preventing their detachment during subsequent catalytic reactions.
[0032] Example 1:
[0033] A method for preparing a TiO2-CoTiO3 hollow nanoreactor includes the following specific steps:
[0034] Step 1: Mix 20 mL of anhydrous ethanol, 40 mL of deionized water, 0.2 mL of ammonia, 100 mg of resorcinol, and 200 μL of formaldehyde solution, stir for 8 hours, centrifuge and wash to obtain RF template microspheres;
[0035] Step 2: Disperse the RF microspheres obtained in Step 1 in 20 mL of anhydrous ethanol, and add 7 mL of acetonitrile, 50 mg of hydroxypropyl cellulose and 0.2 mL of ammonia water. Then add a mixed solution of 1 mL of tetrabutyl titanate-3 mL of ethanol-1 mL of acetonitrile. After stirring for 2 hours, centrifuge and wash to obtain RF@TiO2 core-shell structured material.
[0036] Step 3: Disperse the RF@TiO2 core-shell structured material obtained in Step 2 into 20 mL of 0.2 mol / L NaOH solution, stir for 0.5 hours, centrifuge, and disperse the resulting product in 10 mL of deionized water;
[0037] Step 4: Add 2 mL of 0.5 mol / L cobalt chloride solution to the suspension obtained in Step 3, stir for 12 hours, centrifuge, wash, and dry.
[0038] Step 5: Treat the product obtained in step 4 at 700℃ in air for 4 hours. Disperse the high-temperature treated sample into 20 mL of 0.05 mol / L hydrochloric acid solution, stir for 12 hours, centrifuge, wash, and dry to obtain the TiO2-CoTiO3 hollow nanoreactor.
[0039] Its transmission electron microscope image is as follows Figure 1As shown, the prepared TiO2-CoTiO3 hollow nanoreactor has a hollow structure; HAADF-STEM images and elemental distributions are shown below. Figure 2 As shown, Ti, O, and Co elements are uniformly distributed in the shell structure, indicating that TiO2 and CoTiO3 particles are uniformly composited together; the X-ray diffraction pattern of the synthesized TiO2-CoTiO3 hollow nanoreactor is shown in the figure. Figure 3 As shown, the phase composition is rutile TiO2 and hexagonal CoTiO3. According to the Scherrer formula, the grain sizes of TiO2 and CoTiO3 are 9.3 nm and 12.3 nm, respectively. The grain size of CoTiO3 is significantly smaller than the previously reported submicron size.
[0040] The prepared TiO2-CoTiO3 hollow nanoreactor was used to activate persulfate and degrade tetracycline hydrochloride. Specific application conditions were as follows: 10 mg of the TiO2-CoTiO3 hollow nanoreactor catalyst was weighed and added to 20 mL of a 20 mg / L tetracycline hydrochloride solution. After uniform dispersion, 10 mg of potassium persulfate was added to the system. High-performance liquid chromatography (HPLC) analysis showed that the degradation rate of tetracycline hydrochloride reached over 95% within 30 minutes. The concentration change during the degradation process was as follows: Figure 4 As shown in the figure. Furthermore, the recycling performance of the catalyst was tested; after four cycles, the degradation rate of tetracycline hydrochloride remained above 95% (results are shown in the figure). Figure 5 Under the action of a catalyst alone, the degradation rate of tetracycline hydrochloride was 10% within 30 minutes; under the action of potassium persulfate alone, the degradation rate of tetracycline hydrochloride was 17% within 30 minutes (results as follows). Figure 4 ).
[0041] Comparative Example 1:
[0042] Step 1: Mix 20 mL of anhydrous ethanol, 40 mL of deionized water, 0.2 mL of ammonia, 100 mg of resorcinol, and 200 μL of formaldehyde solution, stir for 8 hours, centrifuge and wash to obtain RF template microspheres;
[0043] Step 2: Disperse the RF microspheres obtained in Step 1 in 20 mL of anhydrous ethanol, and add 7 mL of acetonitrile, 50 mg of hydroxypropyl cellulose and 0.2 mL of ammonia water. Then add a mixed solution of 1 mL of tetrabutyl titanate-3 mL of ethanol-1 mL of acetonitrile. After stirring for 2 hours, centrifuge and wash to obtain RF@TiO2 core-shell structured material.
[0044] Step 3: Treat the RF@TiO2 core-shell structure material obtained in Step 2 at 700℃ for 4 hours in an air atmosphere; thus, obtain the TiO2 hollow nanostructure.
[0045] No cobalt ion exchange was performed during this preparation process, resulting in a single hollow TiO2 nanostructure. The prepared hollow TiO2 nanostructure was used to activate persulfate and degrade tetracycline hydrochloride. Specific application conditions were as follows: 10 mg of the hollow TiO2 nanostructure catalyst was added to 20 mL of a 20 mg / L tetracycline hydrochloride solution. After uniform dispersion, 10 mg of potassium persulfate was added to the system. High-performance liquid chromatography (HPLC) analysis showed that the degradation rate of tetracycline hydrochloride was 24% within 30 minutes. The concentration change during the degradation process is shown below. Figure 4 As shown in the figure. This comparative example illustrates that TiO2 alone is not very effective in activating persulfate to degrade tetracycline hydrochloride.
[0046] Comparative Example 2:
[0047] Step 1: Dissolve 1.25g of cobalt acetate and 1.7mL of tetrabutyl titanate in 30mL of ethylene glycol and react for 5 hours;
[0048] Step 2: Centrifuge and wash the product obtained in Step 1, and dry it at 60°C for 6 hours;
[0049] Step 3: Treat the sample obtained in step 2 at 700°C in air for 4 hours to obtain CoTiO3 particles.
[0050] The prepared CoTiO3 particles were used to activate persulfate and degrade tetracycline hydrochloride. Specific application conditions were as follows: 10 mg of CoTiO3 particle catalyst was weighed and added to 20 mL of a 20 mg / L tetracycline hydrochloride solution. After uniform dispersion, 10 mg of potassium persulfate was added to the system. High-performance liquid chromatography (HPLC) analysis showed that the degradation rate of tetracycline hydrochloride was 48% within 30 minutes. The concentration change during the degradation process is shown below. Figure 4 As shown in the figure. This comparative example illustrates that single CoTiO3 particles are not very effective in activating persulfate to degrade tetracycline hydrochloride, mainly because their particles are large and have few exposed active sites. However, hollow nanoreactors prepared by loading small CoTiO3 particles onto TiO2 hollow nanostructures have excellent persulfate activation performance.
[0051] Example 2:
[0052] A method for preparing a TiO2-CoTiO3 hollow nanoreactor includes the following specific steps:
[0053] Step 1: Mix 40 mL of anhydrous ethanol, 80 mL of deionized water, 0.4 mL of ammonia, 100 mg of resorcinol, and 200 μL of formaldehyde solution, stir for 12 hours, centrifuge and wash to obtain RF template microspheres;
[0054] Step 2: Disperse the RF microspheres obtained in Step 1 in 30 mL of anhydrous ethanol, and add 9 mL of acetonitrile, 60 mg of hydroxypropyl cellulose and 0.4 mL of ammonia water. Then add a mixed solution of 1.5 mL of tetrabutyl titanate, 4.5 mL of ethanol and 1.5 mL of acetonitrile. After stirring for 2 hours, centrifuge and wash to obtain RF@TiO2 core-shell structured material.
[0055] Step 3: Disperse the RF@TiO2 core-shell structured material obtained in Step 2 into 20 mL of 0.3 mol / L NaOH solution, stir for 1 hour, centrifuge, and disperse the resulting product in 20 mL of deionized water;
[0056] Step 4: Add 2 mL of 1.0 mol / L cobalt chloride solution to the suspension obtained in Step 3, stir for 24 hours, centrifuge, wash, and dry.
[0057] Step 5: Treat the product obtained in step 4 at 800℃ in air for 4 hours; disperse the high-temperature treated sample in 20mL of 0.1mol / L hydrochloric acid solution, stir for 16 hours, centrifuge, wash and dry to obtain TiO2-CoTiO3 hollow nanoreactor.
[0058] Catalyst characterization showed that the prepared TiO2-CoTiO3 hollow nanoreactor had a hollow structure, with CoTiO3 nanoparticles uniformly distributed on the surface of the hollow structure. Under the same experimental conditions, it was used to activate persulfate and degrade tetracycline hydrochloride, and the degradation rate of tetracycline hydrochloride remained above 95% within 30 minutes (results are shown in the figure). Figure 6 (As shown).
[0059] Example 3:
[0060] A method for preparing a TiO2-CoTiO3 hollow nanoreactor includes the following specific steps:
[0061] Step 1: Mix 10 mL of anhydrous ethanol, 20 mL of deionized water, 0.2 mL of ammonia, 100 mg of resorcinol, and 100 μL of formaldehyde solution, stir for 8 hours, centrifuge and wash to obtain RF template microspheres;
[0062] Step 2: Disperse the RF microspheres obtained in Step 1 in 20 mL of anhydrous ethanol, and add 7 mL of acetonitrile, 50 mg of hydroxypropyl cellulose and 0.2 mL of ammonia water. Then add a mixed solution of 1 mL of tetrabutyl titanate-3 mL of ethanol-1 mL of acetonitrile. After stirring for 2 hours, centrifuge and wash to obtain RF@TiO2 core-shell structured material.
[0063] Step 3: Disperse the RF@TiO2 core-shell structured material obtained in Step 2 into 10 mL of 0.1 mol / L NaOH solution, stir for 0.5 hours, centrifuge, and disperse the resulting product in 10 mL of deionized water;
[0064] Step 4: Add 1 mL of 0.5 mol / L cobalt chloride solution to the suspension obtained in Step 3, stir for 12 hours, centrifuge, wash, and dry.
[0065] Step 5: Treat the product obtained in step 4 at 600℃ in air for 4 hours; disperse the high-temperature treated sample in 10 mL of 0.01 mol / L hydrochloric acid solution, stir for 8 hours, centrifuge, wash, and dry to obtain the TiO2-CoTiO3 hollow nanoreactor.
[0066] Catalyst characterization showed that the prepared TiO2-CoTiO3 hollow nanoreactor had a hollow structure, with CoTiO3 nanoparticles uniformly distributed on the surface of the hollow structure. Under the same experimental conditions, it was used to activate persulfate and degrade tetracycline hydrochloride, and the degradation rate of tetracycline hydrochloride remained above 95% within 30 minutes (results are shown in the figure). Figure 6 (As shown).
[0067] Example 4:
[0068] A method for preparing a TiO2-CoTiO3 hollow nanoreactor includes the following specific steps:
[0069] Step 1: Mix 40 mL of anhydrous ethanol, 40 mL of deionized water, 0.4 mL of ammonia, 100 mg of resorcinol, and 100 μL of formaldehyde solution, stir for 8 hours, centrifuge and wash to obtain RF template microspheres;
[0070] Step 2: Disperse the RF microspheres obtained in Step 1 in 30 mL of anhydrous ethanol, and add 9 mL of acetonitrile, 60 mg of hydroxypropyl cellulose and 0.2 mL of ammonia water. Then add a mixed solution of 1 mL of tetrabutyl titanate-3 mL of ethanol-1 mL of acetonitrile. After stirring for 2 hours, centrifuge and wash to obtain RF@TiO2 core-shell structured material.
[0071] Step 3: Disperse the RF@TiO2 core-shell structured material obtained in Step 2 into 10 mL of 0.3 mol / L NaOH solution, stir for 1 hour, centrifuge, and disperse the resulting product in 10 mL of deionized water;
[0072] Step 4: Add 1 mL of 1.0 mol / L cobalt chloride solution to the suspension obtained in Step 3, stir for 12 hours, centrifuge, wash, and dry.
[0073] Step 5: Treat the product obtained in step 4 at 800℃ in air for 4 hours; disperse the high-temperature treated sample in 10 mL of 0.1 mol / L hydrochloric acid solution, stir for 8 hours, centrifuge, wash, and dry to obtain the TiO2-CoTiO3 hollow nanoreactor.
[0074] Catalyst characterization showed that the prepared TiO2-CoTiO3 hollow nanoreactor had a hollow structure, with CoTiO3 nanoparticles uniformly distributed on the surface of the hollow structure. Under the same experimental conditions, it was used to activate persulfate and degrade tetracycline hydrochloride, and the degradation rate of tetracycline hydrochloride remained above 95% within 30 minutes (results are shown in the figure). Figure 6 (As shown).
[0075] Example 5:
[0076] A method for preparing a TiO2-CoTiO3 hollow nanoreactor includes the following specific steps:
[0077] Step 1: Mix 30 mL of anhydrous ethanol, 30 mL of deionized water, 0.3 mL of ammonia, 100 mg of resorcinol, and 150 μL of formaldehyde solution, stir for 8 hours, centrifuge and wash to obtain RF template microspheres;
[0078] Step 2: Disperse the RF microspheres obtained in Step 1 in 25 mL of anhydrous ethanol, and add 8 mL of acetonitrile, 55 mg of hydroxypropyl cellulose and 0.3 mL of ammonia water. Then add a mixed solution of 1.2 mL of tetrabutyl titanate, 3.6 mL of ethanol and 1.2 mL of acetonitrile. After stirring for 2 hours, centrifuge and wash to obtain RF@TiO2 core-shell structured material.
[0079] Step 3: Disperse the RF@TiO2 core-shell structured material obtained in Step 2 into 15 mL of 0.2 mol / L NaOH solution, stir for 0.8 hours, centrifuge, and disperse the resulting product in 15 mL of deionized water;
[0080] Step 4: Add 1.5 mL of 0.8 mol / L cobalt chloride solution to the suspension obtained in Step 3, stir for 16 hours, centrifuge, wash, and dry.
[0081] Step 5: Treat the product obtained in step 4 at 750℃ in air for 4 hours; disperse the high-temperature treated sample in 15 mL of 0.06 mol / L hydrochloric acid solution, stir for 10 hours, centrifuge, wash, and dry to obtain the TiO2-CoTiO3 hollow nanoreactor.
[0082] Catalyst characterization showed that the prepared TiO2-CoTiO3 hollow nanoreactor had a hollow structure, with CoTiO3 nanoparticles uniformly distributed on the surface of the hollow structure. Under the same experimental conditions, it was used to activate persulfate and degrade tetracycline hydrochloride, and the degradation rate of tetracycline hydrochloride remained above 95% within 30 minutes (results are shown in the figure). Figure 6 (As shown).
[0083] Example 6:
[0084] A method for preparing a TiO2-CoTiO3 hollow nanoreactor includes the following specific steps:
[0085] Step 1: Mix 25 mL of anhydrous ethanol, 35 mL of deionized water, 0.3 mL of ammonia, 100 mg of resorcinol, and 160 μL of formaldehyde solution, stir for 8 hours, centrifuge and wash to obtain RF template microspheres;
[0086] Step 2: Disperse the RF microspheres obtained in Step 1 in 26 mL of anhydrous ethanol, and add 7.5 mL of acetonitrile, 56 mg of hydroxypropyl cellulose and 0.3 mL of ammonia water. Then add a mixed solution of 1.3 mL of tetrabutyl titanate, 3.9 mL of ethanol and 1.3 mL of acetonitrile. After stirring for 2 hours, centrifuge and wash to obtain RF@TiO2 core-shell structured material.
[0087] Step 3: Disperse the RF@TiO2 core-shell structured material obtained in Step 2 into 12 mL of 0.25 mol / L NaOH solution, stir for 0.6 hours, centrifuge, and disperse the resulting product in 12 mL of deionized water;
[0088] Step 4: Add 1.2 mL of 0.6 mol / L cobalt chloride solution to the suspension obtained in Step 3, stir for 15 hours, centrifuge, wash, and dry.
[0089] Step 5: Treat the product obtained in step 4 at 650℃ in air for 4 hours; disperse the high-temperature treated sample in 12mL of 0.06mol / L hydrochloric acid solution, stir for 15 hours, centrifuge, wash, and dry to obtain the TiO2-CoTiO3 hollow nanoreactor.
[0090] Catalyst characterization showed that the prepared TiO2-CoTiO3 hollow nanoreactor had a hollow structure, with CoTiO3 nanoparticles uniformly distributed on the surface of the hollow structure. Under the same experimental conditions, it was used to activate persulfate and degrade tetracycline hydrochloride, and the degradation rate of tetracycline hydrochloride remained above 95% within 30 minutes (results are shown in the figure). Figure 6 (As shown).
[0091] As demonstrated by the above implementation process, nano-sized perovskite cobalt titanate particles can be uniformly loaded in situ onto the hollow structure of TiO2 through processes such as ion exchange and high-temperature treatment. The large specific surface area of the hollow structure effectively disperses the cobalt titanate nanoparticles, exposing their active sites and exhibiting high catalytic activity and cycle stability in the application of activating persulfate to degrade tetracycline hydrochloride. This invention provides a TiO2-CoTiO3 hollow nanoreactor, its preparation method, and its application, which is expected to offer an effective strategy for dispersing nano-sized cobalt titanate particles and fully utilizing their catalytic activity.
Claims
1. A TiO2-CoTiO3 hollow nanoreactor, characterized in that, The reactor has a hollow structure, and the CoTiO3 nanoparticles have a size of 11~13 nm and are uniformly loaded on the surface of the TiO2 hollow structure. Prepared by the following steps: Step 1: Mix anhydrous ethanol, deionized water, concentrated ammonia, resorcinol, and formaldehyde solution, stir, centrifuge, and wash to obtain RF template microspheres; Step 2: Disperse RF template microspheres in anhydrous ethanol, add acetonitrile, hydroxypropyl cellulose and concentrated ammonia, then add a mixed solution of tetrabutyl titanate-ethanol-acetonitrile, stir for a period of time, centrifuge and wash to obtain RF@TiO2 core-shell structure material; Step 3: Disperse the RF@TiO2 core-shell structured material in NaOH solution, stir for a certain time, centrifuge, and disperse the resulting product in deionized water; Step 4: Add cobalt chloride solution to the suspension obtained in step 3, stir for a period of time, centrifuge and wash, and then dry. Step 5: Treat the product obtained in step 4 at high temperature in air for a period of time, disperse the high-temperature treated sample in hydrochloric acid solution, stir for a period of time, centrifuge, wash and dry to obtain TiO2-CoTiO3 hollow nanoreactor.
2. A method for preparing a TiO2-CoTiO3 hollow nanoreactor, characterized in that, Includes the following steps: Step 1: Mix anhydrous ethanol, deionized water, concentrated ammonia, resorcinol, and formaldehyde solution, stir, centrifuge, and wash to obtain RF template microspheres; Step 2: Disperse RF template microspheres in anhydrous ethanol, add acetonitrile, hydroxypropyl cellulose and concentrated ammonia, then add a mixed solution of tetrabutyl titanate-ethanol-acetonitrile, stir for a period of time, centrifuge and wash to obtain RF@TiO2 core-shell structure material; Step 3: Disperse the RF@TiO2 core-shell structured material in NaOH solution, stir for a certain time, centrifuge, and disperse the resulting product in deionized water; Step 4: Add cobalt chloride solution to the suspension obtained in step 3, stir for a period of time, centrifuge and wash, and then dry. Step 5: Treat the product obtained in step 4 at high temperature in air for a period of time, disperse the high-temperature treated sample in hydrochloric acid solution, stir for a period of time, centrifuge, wash and dry to obtain TiO2-CoTiO3 hollow nanoreactor.
3. The method as described in claim 2, characterized in that, In step 1, the ratio of anhydrous ethanol to resorcinol is 0.1 mL: 1 mg ~ 0.4 mL: 1 mg; the ratio of deionized water to resorcinol is 0.2 mL: 1 mg ~ 0.8 mL: 1 mg; the ratio of concentrated ammonia to resorcinol is 2 μL: 1 mg ~ 4 μL: 1 mg; the mass concentration of formaldehyde solution is 37%, and the ratio of formaldehyde solution to resorcinol is 1 μL: 1 mg ~ 2 μL: 1 mg; the stirring time is 6-12 hours.
4. The method as described in claim 2, characterized in that, In step 2, the ratio of anhydrous ethanol to resorcinol mentioned in step 1 is 0.2 mL:1 mg ~ 0.3 mL:1 mg, and the ratio of acetonitrile to resorcinol mentioned in step 1 is 0.07 mL:1 mg ~ 0.09 mL:1 mg; the mass ratio of hydroxypropyl cellulose to resorcinol mentioned in step 1 is 0.5:1 ~ 0.6:1, and the ratio of concentrated ammonia to resorcinol mentioned in step 1 is 2 μL:1 mg ~ 4 μL:1 mg; in the mixed solution of tetrabutyl titanate-ethanol-acetonitrile, the volume ratio of tetrabutyl titanate, ethanol, and acetonitrile is 1:3:1, and the ratio of tetrabutyl titanate to resorcinol mentioned in step 1 is 10 μL:1 mg ~ 15 μL:1 mg; the stirring time is 2 hours.
5. The method as described in claim 2, characterized in that, In step 3, the concentration of the NaOH solution is 0.1~0.3 mol / L, the ratio of NaOH solution to resorcinol mentioned in step 1 is 0.1 mL:1 mg ~ 0.2 mL:1 mg; the stirring time is 0.5~1.0 hours; the ratio of deionized water used for dispersion to resorcinol mentioned in step 1 is 0.1 mL:1 mg ~ 0.2 mL:1 mg.
6. The method as described in claim 2, characterized in that, In step 4, the concentration of the cobalt chloride solution is 0.5~1.0 mol / L, and the ratio of the cobalt chloride solution to the resorcinol mentioned in step 1 is 10 μL:1 mg ~ 20 μL:1 mg; the stirring time is 12~24 hours.
7. The method as described in claim 2, characterized in that, In step 5, the temperature is maintained at 600-800°C in an air atmosphere. o High temperature treatment for 4 hours; the concentration of hydrochloric acid solution is 0.01~0.1 mol / L, and the ratio of hydrochloric acid solution to resorcinol mentioned in step 1 is 0.1 mL:1 mg ~ 0.2 mL:1 mg; stirring treatment time is 8~16 hours.
8. The application of the TiO2-CoTiO3 hollow nanoreactor as described in claim 1 in the activation of persulfate to degrade tetracycline hydrochloride.
9. The application as described in claim 8, characterized in that, The reaction conditions were: catalyst concentration 0.2~1.0 g / L, persulfate concentration 0.2~1.0 g / L, and tetracycline hydrochloride concentration 5~50 mg / L.
Citation Information
Patent Citations
Preparation method for TiO2 nanomaterial with hollow structure and application thereof
CN105289457A
TiN-Ni photo-thermal catalyst with hollow structure as well as preparation method and application of TiN-Ni photo-thermal catalyst
CN117225452A
